Double‐Layered Metal‐Organic‐Frameworks‐Based Microswimmers for Adaptive Dual‐Drug Anti‐Cancer Therapy Using Artemisinin‐Based Compounds - Yukun Zhong; Haining Li; Teng Jiang; Xueliang Mu; Munetoshi Seki; U Kei Cheang (Advanced Intelligent Systems)
Magnetic microrobots have the potential for anti‐cancer drug delivery; however, using dual‐drug to counter drug resistance, a critical issue in cancer research, has only been briefly investigated. This study introduces the double‐layered metal‐organic‐frameworks (MOFs)‐based microswimmers for sustained dual‐drug delivery. These microswimmers are made up of ZIF‐8 and MIL‐100, biocompatible MOFs, that can selectively adsorb two types of drugs. The MOFs increase the surface area of the microswimmers by ≈2.42 times, which greatly enhances drug adsorption, and improves hydrophilicity, which reduces adhesion for surface locomotion. Their biocompatibility and dual‐drug adsorption are verified through cell viability and drug‐loading tests. The microswimmers have remarkable versatility in loading different drug combinations (DHA + 5‐FU, CPT‐11, or DOX), indicating the potential for adaptive therapy. They can inhibit cancer cells for up to 72 h through the sustained release of dual drugs. In contrast, drug treatments without microswimmers only inhibit cell proliferation for 24 h, leading to a significant rebound. This study provides a method to mass fabricate fully biocompatible microrobots with dual drug loading versatility and high drug adsorption capacity; thus, suggests a powerful platform for sustained adaptive dual‐drug therapy.